2013
DOI: 10.1186/1746-1596-8-84
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of S100A1 in the postmortem diagnosis of acute myocardial infarction

Abstract: BackgroundSudden cardiac death resulting from acute myocardial infarction (AMI) constitutes a significant percentage of the caseload for forensic and clinical pathologists. When sudden death occurs at an early stage (<6 h), pathologists experience difficulty in the postmortem diagnosis of AMI. Because of the specific tissue distribution of S100A1 and its relationship with acute ischemic heart disease, this study aimed to evaluate the performance of S100A1 in the postmortem diagnosis of AMI.MethodsWe constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The contrast results showed that hypoxia could cause the release of S100A1 in damaged cardiomyocytes. This is consistent with the results of Wang et al ‘s, namely, the depleted areas of S100A1 further expanded and S100A1 plasma concentrations further increased with continuation of the hypoxia time [26]. Activated cardiomyocytes can secrete various pro‐inflammatory cytokines and mediators, which may contribute to hypoxic injury in the developing cardiomyocytes dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…The contrast results showed that hypoxia could cause the release of S100A1 in damaged cardiomyocytes. This is consistent with the results of Wang et al ‘s, namely, the depleted areas of S100A1 further expanded and S100A1 plasma concentrations further increased with continuation of the hypoxia time [26]. Activated cardiomyocytes can secrete various pro‐inflammatory cytokines and mediators, which may contribute to hypoxic injury in the developing cardiomyocytes dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…274, 275 Once released, S100A1 activates the surrounding cardiac fibroblasts through TLR4 and triggers the MAPK and NF-κB proinflammatory pathways. 274 However, S100A1 not only promotes proinflammatory signals but also regulates a complex balance between pro- and anti-inflammatory pathways associated with the antifibrotic upregulation of matrix metalloproteinase 9 (MMP9) and the downregulation of type I collagen and connective tissue growth factor.…”
Section: S100mentioning
confidence: 99%
“…Reproduced with permission from [12]. damaged cardiomyocytes in ischemic myocardial tissue [11,28]. A most recent study indicated that extracellular S100A1 is specifically internalized by cardiac fibroblasts transforming them into an immune-modulatory and antifibrotic phenotype via an endosomal TLR4 signaling pathway that beneficially shapes the myocardial healing process [11].…”
Section: S100a1 Expression Regulation and Pathophysiologiesmentioning
confidence: 99%
“…Elevated S100A1 serum levels were reported in patients after open heart surgery and myocardial infarction [55,56] and rapid depletion of S100A1 was subsequently demonstrated in ischemic rat and human myocardium [28]. Among the proteins passively released from damaged cells, distinct molecules may play an active role in the restoration of tissue homeostasis [57].…”
Section: Extracellular S100a1 Targeting Cardiac Fibroblastsmentioning
confidence: 99%